A Systematic Framework for Implementation & Continuous Improvement of Outcome-Based Education (Journal of Advances and Scholarly Researches in Allied Education, 2023)
An emerging pedagogical paradigm, Outcome-Based Education (OBE) places an emphasis on the achievement of predetermined learning outcomes as the cornerstone of all educational activities. The pedagogical approach known as OBE is the subject of this research, which delves into both the theoretical underpinnings & real-world implementation of this approach. Drawing on W. Spady's seminal work from 1994, this essay explores the role of OBE in shaping educational practices, with an emphasis on how to ensure that goals are in line with institutional values & mission statements. This article provides a detailed overview of a methodical procedure for achieving OBE, including all of the necessary steps as well as methods for continuous evaluation & enhancement. Finally, this study piece connects the dots between Outcome-Based Education's theoretical underpinnings or its actual use. It hopes to equip everyone involved in education with the understanding and resources necessary to fully embrace OBE as a paradigm shift in teaching & learning that improves both the quantity and quality of student experiences.